GEOLOGICAL EVIDENCE EXAMINATION USING METHODS OF ENVIRONMENTAL FORENSICS - Zh. Bekzhanov (Теория и практика судебной экспертизы, 2014)
The paper outlines the basics of forensic examination of geological evidence, and arguesfor the need to adopt a standard operating procedure for this type of forensic inquiry.